(untitled) (Research, Society and Development, 2020)
The Cerrado is the second largest Brazilian biome in extension, and in the period from 2002 to 2008, it had the highest annual rate of deforestation among the existing biomes in Brazilian territory. Thus, it is essential to study these areas in search of plants with interesting characteristics for man and consequently for their preservation. Being the species Annona coriacea of great economic potential since its wood has several purposes like boxing and lamination. This research was aimed determine the technical age of cut and radial increments of Annona coriacea. In a savanna area anthropic and green area were selected 15 and 08 individuals respectively, localized in Chapadao do Sul. In the anthropic areas sampled individuals had an average of 21 growth rings / trees having on average 4.06 mm wide, IMRA of 3.48 mm, and ITC to 26 years and five months. Already in green area, showed 22 rings / tree with average width of 3.92 mm, 3.68 mm IMRA of, and ITC close to 26 years.